2017
DOI: 10.1111/ceo.13077
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of visual outcome and the role of early vitrectomy in streptococcal endophthalmitis

Abstract: Early vitrectomy did not influence visual outcome in this cohort. Microbiology results were useful in predicting poor outcomes, and may allow clinicians to make early treatment decisions and provide prognostic information for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 23 publications
(56 reference statements)
3
31
0
2
Order By: Relevance
“…Despite aggressive treatment of the infection, visual outcomes are generally poor. 1 – 9 Kuriyan et al 8 studied 63 cases of streptococcus endophthalmitis over an 11-year period and found that the most common clinical settings were bleb-associated (27%), after intravitreal injection (25%) and after cataract surgery (21%). All patients received intravitreal antibiotics and 22% of the patients underwent pars plana vitrectomy (PPV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite aggressive treatment of the infection, visual outcomes are generally poor. 1 – 9 Kuriyan et al 8 studied 63 cases of streptococcus endophthalmitis over an 11-year period and found that the most common clinical settings were bleb-associated (27%), after intravitreal injection (25%) and after cataract surgery (21%). All patients received intravitreal antibiotics and 22% of the patients underwent pars plana vitrectomy (PPV).…”
Section: Introductionmentioning
confidence: 99%
“…Visual outcomes were generally poor with only 25% having best-corrected visual acuity (BCVA) of 20/400 or better and 25% of the patients had their eyes removed by operations, either evisceration or enucleation. 8 Kurniawan et al 9 studied 101 cases of streptococcus endophthalmitis over a 15-year period and found that 87.1% of the infection occurred postoperatively, and cataract surgery was the most commonly performed operation. Almost all patients had initial intravitreal antibiotics, and 30.7% of the patients underwent vitrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…We read the article by Kurniawan et al . with interest, however, we believe that it deserves further discussion.…”
mentioning
confidence: 90%
“…We thank Grzybowski and Turczynowska for their interest in our recent publication . The Endophthalmitis Vitrectomy Study is now over two decades old, and the criterion of early vitrectomy within 6 h was strictly adhered to as part of this prospective, limited‐time study.…”
mentioning
confidence: 99%